Supplementation of oregano essential oil in the diet reduces oxidative stress in the egg yolk and improves the productive performance of the Japanese quail (Coturnix coturnix japonica) - Loyaga Cortéz, Bruno Saúl (2020)
The aim of this study was to evaluate the effect of supplementation with oregano essential oil in the quail diet on the performance and oxidative stability of the egg. A total of 300 quail, 110 days old, were distributed in five groups: Control (diet without supplementation), E&C (diet plus 0.01% enramycin and 0.025% colistin sulfate) and treatments A, B and C (diets supplemented with 100, 150 and 200 mg/kg of oregano essential oil, respectively). The study was carried out for 12 weeks. The oxidative stability of the egg yolk was evaluated on days 0, 7 and 15 of storage. The results showed that dietary supplementation with essential oil of oregano improved productive parameters compared to control (p<0.05), although it was surpassed by E&C. Group A (100 mg/kg) decreased lipid peroxidation in egg yolk on days 0 (p<0.0001), 7 (p<0.01) and 15 (p<0.0001), with respect to the control and was even better than E&C (p<0.05); however, this effect was not directly related to storage time. In conclusion, oregano essential oil can be a potential nutritional supplement and an antioxidant that would help reduce lipid oxidation in egg yolk and improve certain production parameters.